2018
DOI: 10.3389/fmed.2018.00237
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A1 Phototherapy for Fibrosing Conditions

Abstract: In this article we describe efficacy and safety aspects of ultraviolet A1 (UV-A1) phototherapy in fibrosing conditions. UV-A1 is a specific phototherapeutic modality that is defined by a selective spectral range (340–400 nm). UV-A1 includes distinct modes of action qualifying this method for therapy of a variety of conditions, in particular fibrosing skin diseases. Concerning efficacy of UV-A1 phototherapy in fibrosing conditions, the best evidence obtained from randomized controlled trials exists for localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…However, in some study protocols (particularly for fibrosing conditions) higher doses had been used. 53,54 Our analysis revealed that males have been treated both with significantly higher cumulative UV doses more sessions than females. The same was true for males treated with cabin NB-UVB for pruritus or an autoimmune/inflammatory dermatosis.…”
Section: Discussionmentioning
confidence: 87%
“…However, in some study protocols (particularly for fibrosing conditions) higher doses had been used. 53,54 Our analysis revealed that males have been treated both with significantly higher cumulative UV doses more sessions than females. The same was true for males treated with cabin NB-UVB for pruritus or an autoimmune/inflammatory dermatosis.…”
Section: Discussionmentioning
confidence: 87%
“…[7][8][9][10][11][12][13] The development of UVA 1 phototherapy (340-400 nm) has highly improved treatment of LS. [14,15] Because UVA 1 light is less erythematogenic than broadband UVA, it is possible to apply much higher doses of UVA 1 without the risk of sunburn.UVA 1 light penetrates deeper into the skin than UVB and UVA 2. [16] In the first prospective study on LS, high-dose UVA 1 light (130 J/cm 2 ) was highly effective in reducing skin sclerosis, and some patients even showed complete clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Lowdose to medium-dose UVA 1 phototherapy is usually conducted by means of fluorescent lamp cubicles, that is full-body UV cabins, allowing the irradiation of large body areas; in contrast, metal-halide lamps are more often used for high-dose UVA 1 treatments. [14,18,19] Despite…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet A1 (UV‐A1) phototherapy in the spectral range of 340–400 nm induces increased collagenase activity 4 . Evidence supports its use for fibrosing disorders, including localized scleroderma, lichen sclerosus et atrophicus, and graft‐versus‐host disease 81 . Only a few studies to date have tested UV‐A1 phototherapy in treating keloids in a total of six patients with mixed results 82‐84 …”
Section: Resultsmentioning
confidence: 99%